Pengaruh Promosi, Lingkungan, dan Kompetensi terhadap Kinerja Pegawai pada BKD Prov. Banten - Yogas Adi Pratama; Sahuri Ade Badri; Ubaedah Ubaedah; Haerofiatna Haerofiatna; Ali Imron (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
Performance plays a major role in optimizing public sector organizations, particularly in providing public services. However, performance in optimizing performance is very influenced in other factors, including job promotion, environment, so competence. The purpose is for analyze impact of the promotion, environment, so competence on performance in Banten Provincial Civil Service Agency work unit. The quantitative using saturated sample technique was used for this study,  sample used 79 responden. That iiis obtained through a questionnaire and analyzed by multiple linear. The finally showed that job promotion had a positive with significant impact for performance. The local environment also has a positive and significant impact on performance. The results show that a conducive work environment can increase employee productivity. In addition, employee competence has a positive and significant impact for performance. Together, job promotion, environment, than competence have a significant impact for performance. The overall results show that improving employee performance requires an objective promotion system, a conducive work environment, and continuous competence development.